Maltodextrin improves physical properties and volatile compound retention of spray-dried asparagus concentrate. (May 2021) - Siccama, Joanne W.; Pegiou, Eirini; Zhang, Lu; Mumm, Roland; Hall, Robert D.; Boom, Remko M.; Schutyser, Maarten A.I.
Abstract: Traditional hot air drying of asparagus is known to lead to a powder with a poor aroma profile. We here concentrated asparagus juice into asparagus concentrate (21.7% w/w) and spray-dried it with maltodextrin DE12 as carrier agent to improve the volatile profiles of asparagus powder and to valorise fresh asparagus side-streams. We performed headspace GC-MS with untargeted metabolomics to assess the overall metabolite profile of the spray-dried asparagus powders and identified 70 volatile compounds. The maltodextrin content was positively correlated to the retention of an asparagus key odorant 1-octen-3-ol, as well as other alcohols and aldehydes. Nevertheless, drying conditions had limited effect on the volatile retention of the powders. Moreover, higher outlet temperatures increase the presence of volatiles that were formed during drying, such as 3-methylthio-propanal. From our analyses, it was further found that an increased concentration of maltodextrin was correlated to a lower moisture content, a higher glass transition temperature (Tg ) and a narrower size distribution of the spray-dried powders. The Tg of all powders was described with the Gordon-Taylor equation for multicomponent mixtures, and we found a minimum weight fraction of 0.67 (w/dw) maltodextrin required to obtain glassy asparagus powder for storing at ambient conditions. Highlights: Positive correlation was found between maltodextrin content and aroma retention. Maltodextrin influenced partition coefficient of volatiles between gas/liquid phase. Increasing maltodextrin content improved physical properties of spray-dried asparagus. Higher outlet air temperatures induced volatile formation during drying of asparagus.